Improving Students’ Writing Competency Through The Idea-Details Strategy In Class XI IPA-2 Of SMA Negeri 1 Sukasada In The Academic Year 2016/2017 - Jelantik, I Putu Ngurah Wirabawa (Journal of Education Action Reseach, 2017)
This study was aimed to improve the students’ writing competency in XI IPA-2 at SMA Negeri 1 Sukasada through the implementation of the Idea-Details strategy. The subjects of this study was class XI IPA 2. This study was conducted in form of Classroom Action Research. The data were collected through some instruments, namely writing competency test, questionnaire, and observation checklist. The result showed that the implementation of the Idea-Details strategy was success to improve the students’ writing competency in narrative and report text. The percentage of students who achieved score higher than or equal to 75 increased from 20% in preliminary observation to 85% in cycle 2. The cycle was stopped in cycle 2 since the percentage of the students who achieved the passing score were more than 75% regarded to performance indicator.